2022
DOI: 10.1515/jmbm-2022-0052
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption behaviors of designed metallic square tubes under axial loading: Experiment-based benchmarking and finite element calculation

Abstract: In this article, the load resistance and energy absorptions of thin-walled structures on the square tube were numerically evaluated by the finite element method. This structure can be widely used in automotive industries, industrial buildings, ships, offshore platforms, and airplanes. In the finite element method, thin-walled structures on square tubes were examined with different wall thicknesses and materials. The materials used are mild steel, SAE 1045 steel, and SAE 1008 steel. Using the numerical results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The fluctuations in the load are caused by the formation of successive folding events, in which each subsequent peak corresponds to the onset of a folding process. These phenomena on the maximum load and the folding process, which are related to load fluctuation, are also evident in the case of the tube under compressive load as examined by [26,32,33]. For torsion damage, Germanischer Lloyd (GL), Peschmann, Rice-Tracey, and Cockcroft-Latham (RTCL) produce shear stress at approximately the same stress: 460.44, 460.09, and 459.72 MPa, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The fluctuations in the load are caused by the formation of successive folding events, in which each subsequent peak corresponds to the onset of a folding process. These phenomena on the maximum load and the folding process, which are related to load fluctuation, are also evident in the case of the tube under compressive load as examined by [26,32,33]. For torsion damage, Germanischer Lloyd (GL), Peschmann, Rice-Tracey, and Cockcroft-Latham (RTCL) produce shear stress at approximately the same stress: 460.44, 460.09, and 459.72 MPa, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…It shows that 2 mm mesh has a similar load vs. displacement curve trend compared to the experimental data. It is revealed that mesh size selection is a crucial aspect in terms of numerical modeling verification [26][27][28][29]. specimen geometries and applied load and boundary conditions are determined as shown in Figure 8.…”
Section: Benchmark Resultsmentioning
confidence: 99%
“…The presence of stiffeners in the stiffened plates, which are commonly used in ship structures, had a significant impact on their strength [17]. Maximum force and generated energy are typically used as reference data to assess structural strength in ships [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The FEA model simulates the ship's response to impact loads, such as those encountered during a collision, by dividing the ship's structure into smaller, manageable components called finite elements. These elements are then analyzed using mathematical equations to determine their behavior under different loads [7][8][9][10][11][12]. The results of the analysis can be used to evaluate the strength and integrity of the ship's structure and identify potential areas of weakness that may need to be reinforced.…”
Section: Volume 22 (1) 2023mentioning
confidence: 99%